Human-Tiger Conflicts a Current issue of Central India, Paradigm to Rethink the Consequences and Challenges of changing behaviour of Wild Animals in Human Dominated Landscape - Kumar, Sanjeev (International Journal of Scientific Research in Biological Sciences, 2020)
Human-Tiger conflict or conflict with other wild animals imparts the great challenges for conservation mitigation. Day by day changing cognition and behaviour like movement pattern, killing or preying skills of big cats itself great challenges to resolve. Prey biomass depletion and seasonal variations brings ecological stress in the wild habitat emphasis the adverse movement pattern in human dominated landscapes to get livestock predation in comfortable zone. For this study three important forest division have been opted i.e. Yavatmal, Pusad and Pandharkawada Forest division of Maharashtra India. Last 5 years conflict cases were analyzed along with compensation amount released by forest department.